Impact of energy storage on the stability and transmission efficiency of a remote grid - Romlie, Mohd Fakhizan (2014)
This thesis addresses a remote grid fed by a weak transmission line and a local source of renewable generation. Energy Storage System (ESS) is installed at the remote grid. The thesis investigates the use of the Energy Storage System in improving the overall system efficiency and increasing the power system stability for the transmission line and remote grid system.